Modern approaches to quintessence of public accounting of enterprise in context of economical safety providing - L.V. Gnilitskaya (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Discrepancy of possibilities of modern accounting to the demands of economical safety directed for the satisfaction of informational needs of various groups of users of accounting in order they could make grounded and timely management decisions while providing stable and steady functioning both an enterprise and a region where this enterprise runs and also a state as a whole, has caused the necessity of searching for other concepts and the models of accounting information formation. The research proves that the most advantages for economical safety providing belong to the concept of cost accounting. The use of this concept will allow to identify the information necessary for the sides interested in it; to model external corporation accounting including field peculiarities of an enterprise; to disclose the information concerning not only to internal parameters but also to external environment where the enterprise functions; to assess the risks of businesses and show their influence in corresponding forms of accounting. The adaptation of the concept of cost accounting into the practice of home enterprises (if the informational needs of economical safety are provided) will require definite changes in the structure and contents of accounting information, on one hand, and the improvement (view, shift) of the principles of preparation of accounting as the accounting base, on the other hand.